2022
DOI: 10.1097/ico.0000000000003019
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Safety and Efficacy of Femtosecond Laser–Assisted Descemet Membrane Endothelial Keratoplasty

Abstract: The purpose of this study was to evaluate 5-year safety and efficacy outcomes of femtosecond-enabled Descemet membrane endothelial keratoplasty (F-DMEK) in patients with Fuchs' endothelial dystrophy (FED).Methods: This was a retrospective study, including patients with FED and cataract who underwent either F-DMEK (16 eyes of 15 patients) or manual DMEK (M-DMEK) (42 eyes of 37 patients) combined with cataract extraction. Outcome measures included visual acuity, graft detachment, graft survival, and endothelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Therefore, we included 50 articles in our study (see Appendix 3, Supplemental Digital Content 3, http://links.lww.com/ICO/B504). 8,10,19–66…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we included 50 articles in our study (see Appendix 3, Supplemental Digital Content 3, http://links.lww.com/ICO/B504). 8,10,19–66…”
Section: Resultsmentioning
confidence: 99%
“…[ 1 - 3 , 5 , 6 , 8 - 10 ] Many studies indicated that FSL can potentially improve both the visual and anatomical outcomes after various corneal transplantation surgeries, such as, PK, ALK, EK, and novel techniques including BL transplantation and SLAK. [ 17 , 29 , 44 , 49 - 52 , 68 - 71 , 88 ]…”
Section: Discussionmentioning
confidence: 99%
“…FSL-assisted DMEK was associated with a significantly decreased risk of graft detachment (6.25% vs. 33.3%, P = 0.035) and lower rate of ECD loss with a difference of 8.6% ( P = 0.023), 11.8% ( P = 0.021), 7.6% ( P = 0.088), 5.8% ( P = 0.256), and 13.6% ( P = 0.169) at 1, 2, 3, 4, and 5 years, respectively, than manual DMEK. [ 68 , 69 ] They also showed that FSL-assisted DMEK had a significantly reduced risk of graft detachment (10.0% vs. 65.5%, P = 0.003), rebubbling (10.0% vs. 58.6%, P = 0.011), and primary graft failure (0% vs. 27.6%, P = 0.086) than manual DMEK in eyes with previously failed PK. [ 70 , 71 ] A modified technique, FSL-assisted deep lamellar DMEK, can be a viable option for a particular range of indications, i.e.…”
Section: Femtosecond Laser-assisted Endothelial Keratoplastymentioning
confidence: 99%
See 1 more Smart Citation
“… Retrospective case series- 150 patients 150 eyes Mean age 71.7 ± 13.3 years, Mean preoperative visual acuity 1.09 ± 0.59 LogMAR Secondary glaucoma Conjunctival congestion, corneal edema, and AC reaction Topical steroids and repeat grafting Graft rejection incidence is 2.4% at 1 year and 9.2% at 3 years, Graft failure incidence is 5.5% at 1 year and 16.6% at 3 years 4 Jung et al 88 PLoS One 2022 Jun 30;17(6):e0270037. Retrospective case series- 32 patients 32 patients Mean age 64.5±11.1, mean preoperative LogMAR visual acuity 0.92±0.4 Fuch’s endothelial corneal dystrophy, Pseudophakic Bullous keratopathy Conjunctival congestion, corneal edema, and AC reaction Topical steroids and repeat grafting 4 patients with immunological failure, 2 patients with primary graft rejection 5 Sorkin et al 89 Cornea 2022 Mar 18 Retrospective analysis- 37 patients 42 eyes, Manual DMEK - Fuch’s endothelial corneal dystrophy, Pseudophakic Bullous keratopathy Conjunctival congestion, corneal edema, and AC reaction High-dose topical steroids Primary graft failure-9.5%, Secondary graft failure-0%, graft rejection-7.1% 6 Basak et al 38 Cornea, 2021 Nov 4. Retrospective analysis- 78 patients 80 eyes Mean donor age 83.6 ± 3.7 years (range: 80–100 years), mean recipient age 67.2 ± 6.9 years (range: 60–89 years), the preoperative value of 1.36 ± 0.67 Old age, low endothelial cell count Conjunctival congestion, corneal edema, and AC reaction Topical steroids Graft failure 2 eyes at 1 year, graft rejection 2 eyes, 1 reversed by medical management 7 Besek et al 12 Int Ophthalmol, 2022 Jan;42(1):269–279 Retrospective analysis 150 eyes Fuch’s Corne...…”
Section: Methods Of Searchmentioning
confidence: 99%